Project Report on Marketing Information System - SHAKEEL AHMED and NAVEEN DHAMIJA (1991)
INTERNAL GUIDE: SOMA REDDY E, MVJCE EXTERNAL GUIDE: P ANAND, MANAGER WIPRO INFOTECH LTD
Keywords: Marketing Information System